SYNTHESIS AND CHARACTERIZATION OF COMPLEX Au (THT) Br - Flores C., Rosario (2005)
The complex Au(tht)Br (tht = tetrahydrothiophene) was obtained by reaction of HAuBr4 and tht. This complex was characterized by 1H-RMN, FT-IR and elemental analysis. The stability of this complex is not very good and is degraded very fast by light.